2017
DOI: 10.1039/c6sm02221a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vertical confinement on gelation and sedimentation of colloids

Abstract: We consider the sedimentation of a colloidal gel under confinement in the direction of gravity. The confinement allows us to compare directly experiments and computer simulations, for the same system size in the vertical direction. The confinement also leads to qualitatively different behaviour compared to bulk systems: in large systems gelation suppresses sedimentation, but for small systems sedimentation is enhanced relative to non-gelling suspensions , although the rate of sedimentation is reduced when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Collapse falls into two categories. Rapid collapse, in which the system starts to collapse as soon as it is prepared [210] and delayed collapse in which little happens to the height of the top of the gel for some considerable time until, rather suddenly, it fails catastrophically and collapses in a timescale much shorter than the waiting time [63] [62,205]. Intriguingly, rheological work does suggest a coupling between collapse times, interaction strength and mechanical properties [211].…”
Section: Failure: Collapse Under Gravitymentioning
confidence: 99%
“…Collapse falls into two categories. Rapid collapse, in which the system starts to collapse as soon as it is prepared [210] and delayed collapse in which little happens to the height of the top of the gel for some considerable time until, rather suddenly, it fails catastrophically and collapses in a timescale much shorter than the waiting time [63] [62,205]. Intriguingly, rheological work does suggest a coupling between collapse times, interaction strength and mechanical properties [211].…”
Section: Failure: Collapse Under Gravitymentioning
confidence: 99%
“…The details of the physical mechanisms leading to delayed collapse due to the appearance of cracks in weakly aggregated colloids are still under investigation 11,12,16,[22][23][24][25] . However, recent studies highlighted that the aggregation energy can modify the sedimentation speed in this regime, as well as the time of onset [22][23][24][25] . Therefore, the difference in plasma fibrinogen concentration is likely to explain the further difference in sedimentation speed between NAS patients and healthy controls.…”
Section: Role Of Plasma In the Sedimentationmentioning
confidence: 99%
“…As depicted in Fig. 5D, the ag-262 gregation forces of erythrocytes from acanthocytosis patients 263 in autologous plasma were significantly lower (p = 0.0005) 264 than those from healthy controls.265The details of the physical mechanisms leading to delayed 266 collapse due to the appearance of cracks in weakly aggregated 267 colloids are still under investigation11,12,16,[22][23][24][25] . However, 268 recent studies highlighted that the aggregation energy can 269 modify the sedimentation speed in this regime, as well as the 270 time of onset[22][23][24][25] .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Studies of assembly of so-called "sticky spheres" out of equilibrium, which is a basic model system which undergoes gelation where the colloid-rich phase may crystallise [31], have shown that assembly at different temperatures leads to a complex response of fast yet poorquality assembly upon deep (effective) quenches, and slower but high-quality assembly when the (effective) temperature is higher [32]. This is backed up by experimental work where the system evolved more quickly to its equilibrium demixed state in the case of weak quenches [29,33]. Time-dependent assembly protocols have also been investigated, and it has been found that slow quenches promote high-quality assembly [24], and time-dependent protocols of a deep quench at short times followed by a shallow quench at longer times optimise the process of assembly further [34].…”
Section: Introductionmentioning
confidence: 99%